Perbandingan Holt's dan Winter's Exponential Smoothing untuk Peramalan Indeks Harga Konsumen Kelompok Transportasi, Komunikasi dan Jasa Keuangan - Achmad Fahlevi; Fitra Abdurrachman Bachtiar; Budi Darma Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Consumer Price Index (CPI) is one of the most commonly used indicators in measuring the inflation rate. CPI's group of Transportation, Communication and Financial Services have the second largest proportion on living cost with 19.15%. As the group who categorize as administered price (the price are ruled by the government), forcasting this group would help some parties involved in taking neccessery decision and avoiding significant inflation rate. In this research, forecasting were performed using two Exponential Smoothing method which is, Holt's Exponential Smoothing and Winters Exponential Smoothing. This method was evaluated by calculating average error rate using Mean Absolute Percentage Error (MAPE) method. There will be 120 data from January 2017 until December 2017 that used which taken from Bank Indonesia official websites. The results of the test was the best parameter value for Holt's Exponential Smoothing which is ð›¼ = 0.7 dan Î² = 0.1 and for Winters Exponential Smoothing ð›¼ = 0.1, Î² = 0.4 dan Î³ = 0.8. And from this parameter's value, MAPE's value obtained for Holt's Exponential Smoothing which 0.474% and for Winters Exponential Smoothing is 1.503%. Both of them got MAPE value under 10% that can be categorize as very good on forcasting CPI group of Transportation, Communication and Financial Services. And can be conclude either that Holt's Exponential Smoothing have better accuration rather than Winters Exponential Smoothing in Cosumer Price Index's group of Transportation, Communication and Financial Services.